Application of impressed current cathodic protection to stainless steel hot-water storage tanks - Shirouzu, Tsukasa (Technical series (Nickel Development Institute (Canada)) ;, 1992)
This publication investigated the optimum conditions of cathodic protection - protective potential, current density, current distribution, and electrode positions for SUS304 (type 304, UNS S30408) stainless steel tanks in the anticipated corrosive environment, and have studied the application of an impressed current cathodic protection.